Mengapa Filsafat Perlu Ada di Jantung Pemikiran Civitas Academicus? - Andri Fransiskus Gultom (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2023)
This study aims to reveal the ontological urgency of philosophy for the academic community in higher education. This research uses qualitative methods by conducting verstehen (understanding the text as a posttranslational datum from primary and secondary sources both verbatim and in thick description), trouble mapping (mapping problem sitting), interpretation (interpreting explicit and implicit messages). The results of the study found first, the existence of philosophy exists in forma and materia. Forma, in the onto-epistemological sense i.e. there is a thought anchored as a dialectical logos. Materia, namely, philosophy of existences as a system in the lex generalist curriculum in the form of a course that contains the history of thought (historical discourse) in tension with schemes, between the flow of various statements and variants of disputation. Second, there is a mental readiness to be in tension (in the debate room in the form of scientific rebuttals) for the academic community, both between lecturers and students, fellow lecturers, and fellow students. Thus, psycho-social takes the form of emotions, and action needs to be postponed (epoche) in debate. Rationality, thus, precedes psychological impulses.